Detección molecular de Circovirus porcino 2 y Parvovirus porcino en fetos porcinos abortados de granjas tecnificadas de las regiones de Lima y Amazonas, Perú - Navarro Mamani, Dennis (2025)
The aim of this study was to detect porcine circovirus 2 (CVP2) and porcine parvovirus (PVP) in foetal tissue samples from sows with reproductive problems on pig farms in the Lima and Amazonas regions. Thirty-eight pools of foetal tissue samples (heart, lung, and spleen) from 13 sows collected from September 2020 to October 2021 were used. Molecular detection of CVP2 and PVP was performed using real-time and conventional PCR, respectively. A commercial kit (IDEXX, USA) was used for real-time PCR, and the protocol reported by Zheng et al. (2013) was used for conventional PCR, with slight variations. Abortions occurred in the last (76.9%; 10/13) and second thirds of gestation (23.1%, 3/13). Of the foetal organ pools (P14 and P19), 5.3% (2/38) tested positive for PVP virus in lung samples, and 5.3% (2/38) (P3 and P9) tested positive for CVP-2 in foetal spleen samples. This is the first study in Peru to identify PVP and CVP-2 in aborted foetal tissue.